Control of photoreceptor axon target choice by transcriptional repression of Runt. - Kaminker, J.S.; Canon, J.; Salecker, I.; Banerjee, U. (Nature Neuroscience, 2002)
Drosophila photoreceptor neurons (R cells) project their axons to one of two layers in the optic lobe, the lamina or the medulla. The transcription factor Runt (Run) is normally expressed in the two inner R cells (R7 and R8) that project their axons to the medulla. Here we examine the relationship between Run and the ubiquitously expressed nuclear protein Brakeless (Bks), which has previously been shown to be important for axon termination in the lamina. We report that Bks represses Run in two of the outer R cells: R2 and R5. Expression of Run in R2 and R5 causes axonal mistargeting of all six outer R cells (R1-R6) to the inappropriate layer, without altering expression of cell-specific developmental markers.